Small area study of mortality among people living near multiple sources of air pollution. Issue 9 (September 1998) - Michelozzi, P; Fusco, D; Forastiere, F; Ancona, C; Dell'Orco, V; Perucci, C A
Abstract : OBJECTIVE: In the area of Malagrotta, a suburb of Rome (Italy), a large waste disposal site, a waste incinerator plant, and an oil refinery plant became operational in the early 1960s and have represented three major sources of air pollution. To evaluate the potential health risk due to airborne contamination around these point sources, a small area analysis of mortality was conducted. Cancer of the liver, larynx, lung, kidney, lymphatic, and haematopoietic systems were evaluated. METHODS: Sex and age specific mortality (1987-93) and population denominators (1991) were available for the census tracts of the metropolitan area of Rome. Standardised mortality ratios (SMRs) were computed separately for males and females in bands of increasing distance from the plants, up to a radius of 10 km. Stone's test for the decline in risk with distance was performed with increments in radius of 1 km; SMRs were also computed after adjusting for a four level index of socioeconomic status. RESULTS: No overall excess or decline in risk with distance was found for liver, lung, and lymphohaematopoietic cancers in either sex. For laryngeal cancer, an increased but not significant risk was found at 0-3 km and at 3-8 km. A significant decline with distance in mortality from laryngeal cancer was found among men (p = 0.03); the trend remained after adjusting for the socioeconomic index (p = 0.06). CONCLUSIONS: The study showed no association between proximity to the industrial sites and mortality for most of the several conditions considered. However, mortality from laryngeal cancer declined with distance from the sources of pollution. This result is interesting, as previous findings of an increased risk of laryngeal cancer near incinerators have been controversial.